Direct guidance of Speech Therapy games in the process of speech therapy training - Yuldosheva Dilbarxon Turgunovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The implementation of the process of development of socio-pedagogical work of future speech therapists is intended to regulate its interrelated elements, follow Speech Therapy games in speech therapy classes, direct orientation to the goal, direct leadership of Speech Therapy games in the process of speech therapy training.